The economic value for cycling – a methodological assessment for Starter Cities - Mota, José Carlos Baptista da; Ferreira, João Pedro; Sá, Frederico Moura; Isidoro, Catarina (Hábitat y Sociedad, 2020)
The concerns about climate change, the effects of congestion and pollution in urban areas have led to the debate about the need for alternative mobility patterns in order to reduce the negative impacts of transport. At the same time, research on sustainable urban mobility highlights the value of cycling as a mean of transport and its economic, social and environmental benefits. Despite the proven benefits, investments in cycling are not always considered a priority, especially in contexts where cycling is residual, such as Portuguese cities, with an average modal share of 0.5%. In this context, the Boost project is developing a Starter Cities Roadmap to support planners and local authorities to promote bicycle use. This paper discusses Economic Value for Cycling (EVC) assessment model, developed to analyze the impacts of cycling or the promotion of cycling in the Portuguese economy, namely through the calculation of the bicycle industry value chain; economic impacts of reduced fuel consumption caused by modal shift; and the value of environmental, energy and health benefits at a local level.